Answer:
25.62
Step-by-step explanation:
the answer is rounded and pi was 3.14 to solve this
Answer:
a)= 2
b) 6.324
c) P= 0.1217
Step-by-step explanation:
a) The mean of the sampling distribution of X`1- X`2 denoted by ux`-x` = u1-u2 is equal to the difference between population means i.e = 2 ( given in the question)
b) The standard deviation of the sampling distribution of X`1- X`2 ( standard error of X`1- X`2) denoted by σ_X`1- X`2 is given by
σ_X`1- X`2 = √σ²/n1 +σ²/n2
Var ( X`1- X`2) = Var X`1 + Var X`2 = σ²/n1 +σ²/n2
so
σ_X`1- X`2 =√20 +20 = 6.324
if the populations are normal the sampling distribution X`1- X`2 , regardless of sample sizes , will be normal with mean u1-u2 and variance σ²/n1 +σ²/n2.
Where as Z is normally distributed with mean zero and unit variance.
If we take X`1- X`2= 0 and u1-u2= 2 and standard deviation of the sampling distribution = 6.324 then
Z= 0-2/ 6.342= -0.31625
P(-0.31625<z<0)= 0.1217
The probability would be 0.1217
9514 1404 393
Answer:
a, c, b
Step-by-step explanation:
Collect terms, subtract the constant, divide by the y-coefficient.
(a) 4y + (y - 1) = 29 ⇒ y = 6
(c) (2y + 3) - 4 = 9 ⇒ y = 5
(b) 4y - y + 1 = 13 ⇒ y = 4 . . . . . this equation is not what you have written
__
<em>Additional comment</em>
The second equation suffers from a typo, so your answer may vary.
Answer:
The answer to your question is x ≠ -10 x ≠ 2 x ≠ -2
Solution
Step-by-step explanation:
Process
1.- Factor all the polynomials
= ![\frac{(x-8)(x + 5)}{(x + 10)(x- 2)} / \frac{(x+ 8)(x + 5)}{(x + 10)(x + 2)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-8%29%28x%20%2B%205%29%7D%7B%28x%20%2B%2010%29%28x-%202%29%7D%20%2F%20%5Cfrac%7B%28x%2B%208%29%28x%20%2B%205%29%7D%7B%28x%20%2B%2010%29%28x%20%2B%202%29%7D)
2.- Invert the second term
= ![\frac{(x- 8)(x + 5)}{(x +10)(x - 2)} \frac{(x+ 10)(x + 2)}{(x + 8)(x +5)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-%208%29%28x%20%2B%205%29%7D%7B%28x%20%2B10%29%28x%20-%202%29%7D%20%20%5Cfrac%7B%28x%2B%2010%29%28x%20%2B%202%29%7D%7B%28x%20%2B%208%29%28x%20%2B5%29%7D)
3.- Simplify
= ![\frac{(x- 8)(x + 2)}{(x + 8)(x - 2)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-%208%29%28x%20%2B%202%29%7D%7B%28x%20%2B%208%29%28x%20-%202%29%7D)
4.- x must be different to
x ≠ -10 x ≠ 2 x ≠ -2
This values are from the factor expressions and then equal to zero.